The Effect of SABELS and GRPQ on The Students’ Reading Comprehension at SMA Swasta RK Bintang Timur Pematangsiantar - Parhusip, Megaria (Pascasarjana Universitas HKBP Nommensen, 2021)
The aim of this research is to find out the effect of Scientific Approach-Based on English LearningStrategy (SABELS) and Guided Reading Peer Questioning Strategy (GRPQ) on students’ readingcomprehension at grade X of SMA Swasta RK Bintang Timur Pematang Siantar. The researchersused quantitative method. The mean of GRPQ strategy is 77.50, Standard Deviation is 7.75, andsignificance value is .002 and number of students is 36. The mean in SABELS strategy is 80.00 andstandard deviation is 9.25, and significance value is 0.38 and number of students is 36. The classwho got conventional strategy, it has mean 75.00, standard deviation is 7.50, and significance valueis .000 and number of students is 37. Using t-test in analyzing data, is found that t-value (2,36) ishigher that t-table (1,667) at level of significant 5 %. This means using SABELS is effective todevelop students’ ability in reading comprehension. According to the research findings, it isconcluded that SABELS is more significant than GRPQ Strategy in teaching reading comprehensionat tenth grade students at SMA Swasta RK Bintang Timur Pematangsiantar.